2016
DOI: 10.1002/jcla.22083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of telomere length and insulin-like growth factor-binding protein 7 promoter methylation between breast cancer tissues and adjacent normal tissues in Turkish women

Abstract: These results suggest that IGFBP7 promoter methylation and shorter TL in tumor compared with adjacent tissues may be predictive biomarkers for breast cancer. Telomere maintenance may be indicative of IDC and IDC with HER2 (-) of breast cancer. Further studies with larger number of cases are necessary to verify this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(107 reference statements)
1
0
0
Order By: Relevance
“…Increasing evidence has reported that IGFBP7 expression is regulated by epigenetic changes, especially by DNA methylation in various cancers [16,[30][31][32][33]. In this study, we found a signi cantly negative correlation between the expression of IGFBP7 and methylation levels in GC.…”
Section: Discussionsupporting
confidence: 57%
“…Increasing evidence has reported that IGFBP7 expression is regulated by epigenetic changes, especially by DNA methylation in various cancers [16,[30][31][32][33]. In this study, we found a signi cantly negative correlation between the expression of IGFBP7 and methylation levels in GC.…”
Section: Discussionsupporting
confidence: 57%